2022
DOI: 10.3390/metabo12020167
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Exposure to Di-(2-ethylhexyl) Phthalate (DEHP) Metabolites and Bisphenol A (BPA) and Its Importance for the Prevention of Cardiometabolic Diseases

Abstract: Exposomics analyses have highlighted the importance of biomonitoring of human exposure to pollutants, even non-persistent, for the prevention of non-communicable diseases such as obesity, diabetes, non-alcoholic fatty liver disease, atherosclerosis, and cardiovascular diseases. Phthalates and bisphenol A (BPA) are endocrine disrupting chemicals (EDCs) widely used in industry and in a large range of daily life products that increase the risk of endocrine and cardiometabolic diseases especially if the exposure s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Limit of Detection and Quantification (LOD and LOQ) were determined according to IUPAC guidance and US Environmental Protection Agency (https://www.epa.gov/cwa-methods/procedures-detection-and-quantitation-documents). We found that LOD and LOQ were for MEHP 0.28 and 0.58 ng/ml, for MEOHP 0.18 and 0.48 ng/ml and for MEHHP 0.11 and 0.24 ng/ml, respectively (Carli et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Limit of Detection and Quantification (LOD and LOQ) were determined according to IUPAC guidance and US Environmental Protection Agency (https://www.epa.gov/cwa-methods/procedures-detection-and-quantitation-documents). We found that LOD and LOQ were for MEHP 0.28 and 0.58 ng/ml, for MEOHP 0.18 and 0.48 ng/ml and for MEHHP 0.11 and 0.24 ng/ml, respectively (Carli et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Information on background levels, blank and spike recoveries, calibration curves and quality control samples are reported in (Carli et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical bonds of xenoestrogens with plasma carrier proteins have significantly lower affinity. In natural estrogens, this affinity is much better, so they are more easily accessible to target organs [2,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%